Landscape ecological network construction controlling surface coal mining effect on landscape ecology: A case study of a mining city in semi-arid steppe. (December 2021) - Wu, Zhenhua; Lei, Shaogang; Yan, Qingwu; Bian, Zhengfu; Lu, Qingqing
Graphical abstract: Highlights: Landscape ecological network construction based on the impact of surface coal mining on landscape ecology. Resistance surface model based on multi-regulation integration. One-ring, Two-vertical, Two-horizontal, Eight-core, Ten-node, and Multi-corridor. The landscape ecological network constructed in this study is helpful for the self-restoration of mining cities. Abstract: Surface coal mining leads to a series of landscape ecological disturbances and ecological environmental problems. Landscape ecological network plays an important role in maintaining ecological balance, protecting biodiversity, preventing pollution diffusion, and increasing landscape connectivity. However, previous studies on the landscape ecological network of mining cities have not thoroughly considered the impact of mining on landscape ecology. This study proposed a framework of landscape ecological network construction controlling surface coal mining effect on landscape ecology. The minimum cumulative resistance model was used to simulate the landscape ecological network by constructing a resistance surface based on the multi-regulation integration. The newly constructed landscape ecological network is helpful for improving the landscape function of the mining areas, preventing the impact process of mining, and the self-restoration of mining cities in semi-arid steppes. The research results can provide a reference for the ecological restoration, urban planning, and landscape ecological management of mining cities in semi-arid steppes.